Control and operation of modular multilevel converters - Yang, Shunfeng (2018)
The increasing trend of electrical power demands in megacities, industries and transportation requires medium- or high-voltage power electronics devices to serve as the enabling components for high power conversion, due to design flexibility, better dynamic performance, energy efficiency and environment friendliness. Multilevel power converters, such as Neutral Point Clamped (NPC) Converters, Cascaded H-Bridge (CHB) Converters and Modular Multilevel Converters (MMCs), are popular commercialized candidates for such high power applications. Among them, the MMC possesses great performance in terms of functionality, hardware implementation, configuration complexity, output power quality, efficiency and reliability, and it shows considerable research potential in the academic world as well. This thesis aims to investigate the control and operation strategies that related to the efficiency, nonlinearity, modularity and reliability of MMCs.